Spies and the Virus: The COVID-19 Pandemic and Intelligence Communication in the United States - Lankford, Ana Maria; Storzieri, Derrick; Fitsanakis, Joseph (Frontiers in Communication, 2020)
This paper introduces a crucial parameter to the novel coronavirus response in the United States, by shedding light on the early-warning role of intelligence agencies. It argues that the intelligence components of the federal government’s Biological Defense Program offered actionable forewarning about an impending pandemic in the years leading to the COVID-19 outbreak. Yet, almost from the opening stages of the pandemic, senior government officials, including President Donald Trump, have repeatedly claimed that the virus “came out of nowhere” and that “nobody saw it coming”. We show that these assertions contradict more than 15 years of pandemic preparedness warnings by intelligence professionals, and disregard the existence of intelligence-led federal pandemic response strategies of every US administration in our time. However, rather than simply placing blame on the White House for discounting these warnings, we advance a conceptual analysis of what many in the US Intelligence Community view as a critical breakdown in strategic communication between intelligence professionals and key government decision-makers. This study agrees with those who suggest that the White House disregarded its own pandemic experts. However, it also posits that the means of strategic communication employed by intelligence experts to alert the White House to the threat were unproductive. These alerts were communicated largely through the President’s Daily Brief, an archaic and ineffectual method of communication that is not designed to facilitate the kind of laser-focused, unequivocal exchange of information needed when potentially catastrophic threats confront the world. This study suggests that the Intelligence Community must implement more direct, immediate and conclusive methods of communicating intelligence to decision-makers, and should seriously consider creating a new line of products that addresses existential challenges to national security. Lastly, we contend it is time to re-evaluate existing rules that prevent intelligence analysts from offering advice on policy. Although we agree that intelligence professionals should refrain from providing policy advice on routine matters, we question the value of preventing these highly knowledgeable experts from communicating strategic policy advice to decision-makers when it comes to threats of a catastrophic nature, which may prove potentially existential for the US, its allies, and the world.